Constitutional Court Decisions in Judicial Review of Laws Against the 1945 Constitution (2024–2025) - Irmanjaya Thaher; M. Abyan Mufid; Mariani Wiwik (Yayasan Lembaga Studi Makwa, 2024)
This article examines the development of constitutional adjudication in Indonesia through an analysis of the Constitutional Court’s judicial review decisions issued during the 2024–2025 period. It focuses on four significant rulings: Constitutional Court Decision No. 144/PUU-XXIII/2025 concerning the State Treasury Law, Constitutional Court Decision No. 62/PUU-XXII/2024 concerning the State Treasury Law, Constitutional Court Decision No. 105/PUU-XXII/2024 concerning the Information and Electronic Transactions Law, and Constitutional Court Decision No. 16/PUU-XXI/2023 concerning the National Capital City Law. Using a normative legal research method supported by statutory, conceptual, and case approaches, the study evaluates the legal reasoning adopted by the Court in determining the constitutionality of statutory provisions. Particular attention is given to the petitioners’ legal standing, the interpretation of constitutional norms, the substance of judicial review, and the role of majority and dissenting opinions in shaping constitutional jurisprudence. The analysis demonstrates that these decisions reflect an evolving constitutional framework in which the Constitutional Court increasingly functions as the guardian of constitutional supremacy and the protector of fundamental rights. The rulings also illustrate the Court’s effort to balance legal certainty, democratic governance, and public accountability while responding to contemporary constitutional challenges. Furthermore, dissenting opinions enrich constitutional discourse by offering alternative interpretations that may influence future judicial developments and legislative reform. Overall, the examined decisions indicate a continuing maturation of Indonesia’s constitutional system through more comprehensive constitutional reasoning, greater protection of citizens’ constitutional rights, and the reinforcement of judicial professionalism, transparency, and institutional legitimacy in exercising the power of constitutional review.